ChemInform Abstract: Synthesis of a New Class of Iminosugars Based on Constrained Azaspirocyclic Scaffolds by Way of Catalytic C—H Amination. Issue 3 (29th December 2015) - Nocquet, Pierre‐Antoine; Hensienne, Raphael; Wencel‐Delord, Joanna; Wimmer, Eric; Hazelard, Damien; Compain, Philippe
Abstract: Iminosugars (VI) and (VII) are synthesized from substrate (I) via Rh‐catalyzed intramolecular amination followed by N‐allylation, metathesis reaction, and either hydrogenation/deprotection or dihydroxylation/deprotection sequences.